Application of polyoxometalate-ionic liquids (POM-ILs) in dye-sensitized solar cells (DSSCs) - Cruz, Hugo (2020)
project “SunStorage- Harvesting and storage of solar energy”, with reference POCI-01-0145-FEDER-016387, and by national funds (PTDC/ QEQ-QFI/1971/2014), through FCT - Fundação para a Ciência e a Tecnologia. H. Cruz thanks to Fundacão para a Ciência e a Tecnologia, MCTES, for the norma transitória DL 57/2016 Program Contract. L. C. Branco thanks to financial support of FCT/MCTES IF/0041/2013/CP1161/CT00). Ana Lucia Pinto thanks to FCT/MCTES for the grant PD/BD/135087/2017